157k views
1 vote
The graph of a function g is shown below. Use the graph of the function to find its average rate of change from x = - 6 to x = 2 Simplify your answer as much as possible .

The graph of a function g is shown below. Use the graph of the function to find its-example-1
User Mudar
by
4.7k points

1 Answer

6 votes

The average rate of change of a function between the values x=a and x=b is:


(g(b)-g(a))/(b-a)

In this case a=-6 and b=2; from the grapg we notice that g(-6)=-1 and that g(2)=-1; plugging these values we have:


(-1-(-1))/(2-(-6))=(-1+1)/(2+6)=(0)/(8)=0

Therefore, the average rate of change is 0

User Vectorsize
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.